Gambaran Kadar Debu Total Dan Gangguan Fungsi Paru Pada Tenaga Kerja Di Unit Pengantongan Semen PT. Semen Tonasa Gudang Arang Kota Ambon - Nurul A. B Kalauw; Rahma Tunny; Abd. Rijali Lapodi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Dust is solid particles caused by natural or mechanical forces such as processing, crushing, softening, rapid packing, blasting, etc. from organic or inorganic materials.Many solid particles are produced by various industries, one of which is the cement industry which has an impact on air pollution by dust. The aim of this research is to determine the description of total dust levels and lung function disorders in workers in the cement Packagingunit at PT.CementTonasa Gudang Arang, Ambon City. This type of research is analytical observation,using a cross sectional study design method that is each object is only observed once and measurements are carried out simultaneously. The research results were obtained from measuring dust levels at three points, namely the packing room.21.7, loading space 20.5 and loading and unloading space 17.4, which is already exceeding the threshold value. And the results of lung function examinations on workers showed that 10 workers had disorders in the mild restrictive category, 6 workers had mild obstructive disorders, and 2 combined and 14 workers had no disorders in the normal category. The results of this study showed that dust levels had exceededthreshold value, it is known that the highest dust content is in the packing room at 21.7 mg/Nm3 and the lowest is in the loading and unloading room at 17.4 mg/Nm3. The lung function capacity of the workforce shows that 10 workers have lung function disorders in the restrictive category, 6 workers have obstructive, 2 combined and 14 workers have no disorders (normal).